Cross-border effects of capacity mechanisms: Do uncoordinated market design policies countervail the goals of European market integration? - Roland Meyer; Olga Gore (Jacobs University Bremen, Bremen Energy Research (BER), 2014)
This article analyses cross-border effects of capacity mechanisms and discusses whether such mechanisms countervail the goals of European Market Integration. Using a two-country-model, the countries' policy options are analysed from a game-theoretical viewpoint. A model simulation identifies the main effects on investments, trade, and overall welfare. We find that a strategic reserve and reliability options have both negative cross-border effects if implemented unilaterally. This exerts pressure on the neighbouring country to change its market design as well. Given that both countries chose their optimal market design, however, the Nash Equilibrium is welfare improving from an overall point of view. Reliability options are superior to a strategic reserve as they avoid a non-market-based dispatch of generation and thus increase market trade and welfare. Furthermore, surpluses are redistributed from producers to consumers, which serves overall welfare if the focus is on consumer benefits.
Keywords: D47; L11; L52; L94; 330; Market design; Generation adequacy; capacity mechanisms; Internal European market